ROMANTICIZING ILLNESS: THE REPRESENTATION OF LOVE AND DISEASE IN THE MOVIES 'MIDNIGHT SUN' AND 'MEET ME AFTER SUNSET' - Aurachel Umara; Danial Hidayatullah (UIN Raden Mas Said Surakarta, 2025)
This study aims to find out how love and disease are represented as discourse in the movies entitled Midnight Sun (2018) and Meet Me After Sunset (2018). How the discourse of disease and love is constructed simultaneously in the stories of two characters with different social and cultural backgrounds is crucial to probe because discourses convey and create power and hierarchy. This study compares two characters who suffer from a rare disease named xeroderma pigmentosum. The disease makes them sensitive to sunlight in the teenage phase during which they experience falling in love. The main objects of comparison are the movie characters Katie from Midnight Sun and Gadis in Meet Me After Sunset. This study employs comparative methods which are appropriate to analyze how different socio-cultures can influence the discourse on love and illness. Discourses and constructs regarding love and illness in popular literature, including movies, cannot be fully understood without referring to gender and socio-culture. Illness is romanticized in Meet Me After Sunset and Midnight Sun. In the Indonesian context, the discourse of love as freedom is less obvious. In contrast, the discourse of isolation and the lack of agency are more advocated compared to the American counterpart. It is due to the differences in cultural patterns that operate in both movies. The discourse of illness in both stories leads to a binary gender hierarchy that associates masculinity with health, while femininity is associated with illness. The isolation caused by disease can also be associated with domestic femininity, which then becomes the idealized value of femininity in both movies.